Morphological study of the development of abrasion ring around the edges of the input gunshot wounds subject to the provisions of theoretical mechanics - Mishalov, V. D.; Michailenko, O. V.; Grynchyshyna, O. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. According to most authors, the mud pies abrasion with gunshot damage is a destroyed epidermis at the edges of the skin defect, which forms the ball onto the path of penetration in the thickness of the layers of the skin and body tissue. Therefore, no complete explanation of the stages and mechanism of formation of the abrasion ring around the edges of the skin defect at the entrance gunshot gunshot wound in contact with the projectile at right angles. Objective. The objects of the study were entrance gunshot wounds, which were formed as a result of shots with bullets of 9 mm caliber, obtained from archival material of the Bureau of forensic medical examination and experimentally obtained gunshot injuries of blocks of sculptural plasticine 9 mm with elastic spherical shells. Methods. Research methods were applied: morphological, medical-criminalistic, visual, analytical and comparative. Data of theoretical mechanics were used to estimate the mechanics of skin destruction. Results. In the study of entrance gunshot wounds, which were formed when a bullet hit the body at a right angle, around its defect was found abrasions in the form of a zone irregular rounded shape, with the bottom of a brownish-brown color. That is, the area of the skin that corresponded to the localization of the abrasion was represented by the naked surface of the dermis, with no reduction in the thickness of the dermis itself. In experimental shots in blocks of sculpted clay elastic shells of spherical shape with a distance of 2 m were formed damage incorrectly rounded in shape, had deepened the crater bottom, with depths ranging from 22.0 mm to end-to-end damage to the block of clay. In not injuries through the clay, formed of the cavity criterion forms on the inner surface was discovered prints bullet round shape. The edges of the walls of the cavity had a thinned appearance, were turned outwards, radially oriented breaks of plasticine were determined at their edges, due to which the damage as a whole took the form of a "crown". In the future, the stages of formation of damage to the block of plasticine, which was formed from the action of an elastic spherical projectile, were considered from the standpoint of theoretical mechanics. Conclusion. The formation of the abrasion perimeter is not associated with mechanical contact interaction (friction) of the lateral surface of the bullet and the skin, and its formation is a consequence of the detachment of the epidermis along the edge of the skin defect of the entrance gunshot wounds, due to the complex shock-wave process, which in the initial stages includes the formation of a temporary cavity in the form of a funnel and the further spread of surface Rayleigh waves, accompanied by a detachment of the epidermis.